External awareness and GABA—A multimodal imaging study combining fMRI and [18F]flumazenil‐PET. Issue 1 (21st September 2012) - Wiebking, Christine; Duncan, Niall W.; Qin, Pengmin; Hayes, Dave J.; Lyttelton, Oliver; Gravel, Paul; Verhaeghe, Jeroen; Kostikov, Alexey P.; Schirrmacher, Ralf; Reader, Andrew J.; Bajbouj, Malek; Northoff, Georg
<x xml:space="preserve">Abstract</x> Awareness is an essential feature of the human mind that can be directed internally, that is, toward our self, or externally, that is, toward the environment. The combination of internal and external information is crucial to constitute our sense of self. Although the underlying neuronal networks, the so‐called intrinsic and extrinsic systems, have been well‐defined, the associated biochemical mechanisms still remain unclear. We used a well‐established functional magnetic resonance imaging (fMRI) paradigm for internal (heartbeat counting) and external (tone counting) awareness and combined this technique with [18F]FMZ‐PET imaging in the same healthy subjects. Focusing on cortical midline regions, the results showed that both stimuli types induce negative BOLD responses in the mPFC and the precuneus. Carefully controlling for structured noise in fMRI data, these results were also confirmed in an independent data sample using the same paradigm. Moreover, the degree of the GABAA receptor binding potential within these regions was correlated with the neuronal activity changes associated with external, rather than internal awareness when compared to fixation. These data support evidence that the inhibitory neurotransmitter GABA is an influencing factor in the differential processing of internally and externally guided awareness. This in turn has implications for our understanding of the biochemical mechanisms underlying awareness in general and its potential impact on psychiatric disorders. Hum Brain Mapp 35:173–184, 2014. © 2012 Wiley Periodicals, Inc.